Elit Politik Lokal dalam Perubahan Sistem Politik - - Haryanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2009)
The changing Indonesian political structure since the collapse of New Order Regime in 1998 has brought opportunity for local political elites. This article, using Giddens’ theory on structuration discusses how local political elites perceive the new political structure and exploit it in order to get power.